Single case research methodology applications in special education and behavioral sciences - Gast, David L.; Ledford, Jennifer R. (Routledge, 2014)
In this new edition the authors detail why and how to apply standard principles of single case research methodology to one's own research or professional project. Using numerous and varied examples, they demonstrate how single case research can be used for research in behavioral and school psychology, special education, speech and communication sciences, language and literacy, occupational therapy, and social work.